2009
DOI: 10.1111/j.1365-2265.2009.03621.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of congenital goitres with hypothyroidism caused by defective thyroglobulin synthesis. Identification of a novel c.7006C>T [p.R2317X] mutation and expression of minigenes containing nonsense mutations in exon 7

Abstract: In this study, we have identified a novel nonsense mutation p.R2317X in the acetylcholinesterase homology domain of TG. We have also observed that nonsense mutations do not interfere with the pre-mRNA splicing of exon 7. The results are in accordance with previous observations confirming the genetic heterogeneity of TG defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
2
33
1
Order By: Relevance
“…The p.R277X mutation is the most frequently reported mutation in the TG gene and affected individuals are either homozygous or compound heterozygous mutations [41,44,45,48,49,53,55,57,58]. This mutation has been found in families from Brazil, Argentina, Galicia and France [41,44,45,48,49,53,55,57,58].…”
Section: Tg Mutations and Congenital Hypothyroidismmentioning
confidence: 99%
See 3 more Smart Citations
“…The p.R277X mutation is the most frequently reported mutation in the TG gene and affected individuals are either homozygous or compound heterozygous mutations [41,44,45,48,49,53,55,57,58]. This mutation has been found in families from Brazil, Argentina, Galicia and France [41,44,45,48,49,53,55,57,58].…”
Section: Tg Mutations and Congenital Hypothyroidismmentioning
confidence: 99%
“…Fifty-two mutations have been identified and characterized in the human TG: 11 splice site mutations, 11 nonsense mutations, 23 missense mutations, 6 deletions (5 single and 1 involving a large number of nucleotides) and 1 single nucleotide insertion [10,11,12,13,14,15,17,30,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58] (table 1; fig. 2, 3).…”
Section: Tg Mutations and Congenital Hypothyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first description of TG gene mutations in patients with congenital goiter and hypothyroidism (Ieiri et al, 1991), at least 50 different mutations have been found scattered in most of the coding exons of the human TG gene: including 23 missense mutations,10 nonsense mutations, five single and one large nucleotide deletions, one single nucleotide insertion, and 10 splice site mutations (Machiavelli et al, 2010;Targovnik et al, 2010). These findings suggest that the recessive form of this disease results, to different degrees, from loss of function of normal protein.…”
Section: Discussionmentioning
confidence: 99%